2021
DOI: 10.28932/jmh.v3i1.3145
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Torbangun Leaf Powder (Coleus amboinicus L) in Increasing Prolactin in Breastfeedings Wistar Rats and Bodyweight of the Litters

Abstract: Research on local herbs that have the effect of increasing breast milk production isneeded to help mothers with insufficient breastmilk. This research was conducted to determinethe effect of torbangun (Coleus amboinicus L) leaf powder in increasing prolactin inbreastfeeding Wistar rats and the bodyweight of the litters. Thirty breastfeeding Wistar rats weredivided into 5 groups with 5 litters each. The treatments given were 108 mg, 216 mg, and 432 mgtorbangun leaf powder (TLP), with domperidone as the positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…18 A study showed a signifi cant difference in prolactin levels in breastfeeding Wistar rats after being given processed foods containing galactogogue with a p-value of 0.000. 24 Flavonoids in 100 grams of processed cassava leaves jerky are somewhat higher, namely 1.988 grams compared to 0.8371 grams of katuk leaves. This was because fl avonoids, components of phytochemical compounds in cassava leaves, are chemical messengers delivered by the bloodstream to the tissues to stimulate or inhibit a process.…”
Section: Discussionmentioning
confidence: 97%
“…18 A study showed a signifi cant difference in prolactin levels in breastfeeding Wistar rats after being given processed foods containing galactogogue with a p-value of 0.000. 24 Flavonoids in 100 grams of processed cassava leaves jerky are somewhat higher, namely 1.988 grams compared to 0.8371 grams of katuk leaves. This was because fl avonoids, components of phytochemical compounds in cassava leaves, are chemical messengers delivered by the bloodstream to the tissues to stimulate or inhibit a process.…”
Section: Discussionmentioning
confidence: 97%
“…The suggested dosage for lactating mothers was 3x50 g torbangun simplicia per day, and the LD 50 (50% lethal dose) was more than 5000 mg/kg of body weight in the rat (Kemenkes, 2016). Table 3 summarized selected in vivo studies of torbangun leaves as a galactagogue using lactating rats (Damanik et al, 2017;Hasianna et al, 2021;Hutajulu and Junaidi 2013;Iwansyah et al, 2017) and humans (Herlina, 2018;Santosa, 2001). Hasianna et al (2021) showed that 432 mg of dried torbangun leaves had the most signifi cant effect on increasing prolactin level compared to the negative control, 108 mg, and 216 mg of dried torbangun leaves.…”
Section: Torbangun Leafmentioning
confidence: 99%
“…Table 3 summarized selected in vivo studies of torbangun leaves as a galactagogue using lactating rats (Damanik et al, 2017;Hasianna et al, 2021;Hutajulu and Junaidi 2013;Iwansyah et al, 2017) and humans (Herlina, 2018;Santosa, 2001). Hasianna et al (2021) showed that 432 mg of dried torbangun leaves had the most signifi cant effect on increasing prolactin level compared to the negative control, 108 mg, and 216 mg of dried torbangun leaves. There was no signifi cant difference in the weight gain of the pups.…”
Section: Torbangun Leafmentioning
confidence: 99%